Physicochemical, in vitro bile-acid binding and hypoglycaemic properties of red pitaya (Hylocereus polyrhizus) peel pectin - Al-Ezzi, Majida; Muhammad, Kharidah; Gannasin, Sri Puvanesvari; Hamzah, Mohd Yusof; Shukri, Radhiah; Carew, Irene (Elsevier, 2024)
Physicochemical properties and cholesterol-lowering potential of high methoxyl pectin extracted from pitaya peel (PP) using citric acid, microwave-assisted extraction (MAE) and ultrasound-assisted extraction (UAE) techniques have been reported. Enzyme-assisted citric acid extraction and its effect on the yield, physicochemical, technological, in vitro bile-acid binding and hypoglycaemic properties of PP pectins (PPP) were investigated and reported for the first time in this study. Pectins were extracted from whole PP using distilled water (DW) and different concentration levels of citric acid (CA) (0.5, 1.0, 1.5, and 2) with the aid of cellulase (C) enzyme. The characteristics of PPP were determined and compared to that of commercial citrus pectins (HS-R, HS-ES, and LC-S18). The PPP extract extracted with C1.5CA had the highest yield (24.63), degree of esterification (50.20), water-holding capacity (7.53 g water/g dry sample), oil-holding capacity (2.17 g oil/g dry sample), intrinsic viscosity, emulsifying activity (100) and emulsion stability (100). Good physicochemical properties of the C1.5CA-PPP extract can be associated with its notable in vitro bile acid-binding capacity and glucose-binding capacity. The findings indicate that the cellulase-assisted 1.5 citric acid (C1.5CA) extracted PPP has noteworthy physicochemical, hypocholesterolemic and hypoglycaemic properties. Thus, it could be a suitable alternative food ingredient for the management of high blood cholesterol and Type 2 diabetes mellitus.